The Discrepancy Effect of Strategy, Environment, Size and Centralization on Budgetary Characteristics - Majdy Zuriekat; Husam Abu Khadra; Nidal Alramahi (Journal of Accounting, Business and Management (JABM), 2009)
Budget is a form of organizational control that has always popularity over decades. However, there has been limited research that studied the characteristics of budgets in Jordanian settings in general and the service sector in particular. To advance our knowledge of the characteristics of budgets (i.e. budgetary practices and budgetary usage), this study examines the relationship between two aspects of business strategy (cost leadership and differentiation), environmental unpredictability, organization size, and centralization and the characteristics of budgets on a sample of Jordanian Banks and Insurance Companies. The results using confirmatory factor analysis (CFA) and multiple regression indicate that cost leadership strategy, environmental unpredictability and organization size have significant influence on budgetary system characteristics (i.e. practices and usage). This paper adds to the growing knowledge on budgetary system characteristics in contingency framework relationships.